2014
DOI: 10.1038/ncomms6310
|View full text |Cite
|
Sign up to set email alerts
|

Passive appendages generate drift through symmetry breaking

Abstract: Plants and animals use plumes, barbs, tails, feathers, hairs and fins to aid locomotion. Many of these appendages are not actively controlled, instead they have to interact passively with the surrounding fluid to generate motion. Here, we use theory, experiments and numerical simulations to show that an object with a protrusion in a separated flow drifts sideways by exploiting a symmetry-breaking instability similar to the instability of an inverted pendulum. Our model explains why the straight position of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
60
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 26 publications
(36 reference statements)
8
60
1
Order By: Relevance
“…Extending work of Bagheri et al [20], Lacis et al [21] showed the symmetry-breaking instability is similar to the instability of an inverted pendulum. Note that these studies considered very low values of structure-fluid density ratio ((0.1)) as well as flexural rigidity ((0.001)-(0.1)), which is two-three orders of magnitude lesser than the values used in the present study.…”
Section: Studies On Steady/pulsatile Inflow Past Flexible Thin Structmentioning
confidence: 79%
“…Extending work of Bagheri et al [20], Lacis et al [21] showed the symmetry-breaking instability is similar to the instability of an inverted pendulum. Note that these studies considered very low values of structure-fluid density ratio ((0.1)) as well as flexural rigidity ((0.001)-(0.1)), which is two-three orders of magnitude lesser than the values used in the present study.…”
Section: Studies On Steady/pulsatile Inflow Past Flexible Thin Structmentioning
confidence: 79%
“…These often make use of passive appendages attached to their bodies (plumed seeds, barbs, tails, and protrusions) to generate locomotion [7,8,9]. Recently, Lācis et al [7] demonstrated that the interaction between the wake of a falling bluff body and a protrusion clamped to its rear end can generate a sidewards drift by means of a symmetry-breaking instability similar to that of an inverted pendulum.…”
mentioning
confidence: 99%
“…An example highlighting the non-trivial role of a passive appendage on the behavior of solid objects is discussed by Lacis et al (2014), where it is shown how the appendage interacts with the wake, thus changing the flow structure and, in turn, the system's dynamics. Using simple concepts, one could argue that adding a filament to the rear of the pendulum increases added mass effects, which, according to Eq.…”
Section: Control Of the Instabilitymentioning
confidence: 99%
“…Besides its applicability, the fluid-structure interaction poses fundamental problems. For example, recent studies have outlined a symmetry breaking mechanism that, so far, has eluded our intuitive understanding of how flows affect the shape and conformation of flexible objects (Bagheri et al, 2012;Lacis et al, 2014).…”
Section: Introductionmentioning
confidence: 98%